2012
DOI: 10.5539/gjhs.v4n5p20
|View full text |Cite
|
Sign up to set email alerts
|

The Intensity of Intensive Care: A Patient’s Narrative

Abstract: This qualitative study involved action research to explore one woman’s narrative of awareness, emotions and thoughts during treatment in an intensive care unit (ICU). The overarching aim is to increase insight into the thoughts, feelings and bio-psychosocial needs of the patient receiving treatment in ICU. Data was collected by means of narrative discourse analysis. Literature on the psychosocial and spiritual implications of ICU treatment is limited, and often patients have no recall of their treatment in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In most studies, several symptoms were identified (Stoll et al, 1999;Jones et al, 2004 2006; Myhren et al, 2009;Myhren et al, 2010aMyhren et al, , 2010bPeris et al, 2011;Garrouste-Orgeas et al, 2012;Wade et al, 2012;Rosendahl et al, 2013), whereas in others fewer symptoms were found, although still more than seen in the general population (Schelling et al, 1998;Cuthbertson et al, 2004;Nickel et al, 2004;Girard et al, 2007;Samuelson et al, 2007;Davydow et al, 2013;Svenningsen, 2013). In some studies, prior psychiatric disease was correlated with PTSD after ICU discharge (Nickel et al, 2004;Davydow et al, 2013), but not in all (Svenningsen, 2013), and anxiety and depression are sometimes described in combination with PTSD (Jones et al, 2004;Myhren et al, 2009;Myhren et al, 2010aMyhren et al, , 2010bGarrouste-Orgeas et al, 2012;Herbst and Drenth, 2012;Davydow et al, 2013;Rosendahl et al, 2013). In one qualitative study, patients suffering from PTSD described a need to make sense of their traumatic memories, and the transformation of one's self (Corrigan et al, 2007).…”
Section: Mental Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies, several symptoms were identified (Stoll et al, 1999;Jones et al, 2004 2006; Myhren et al, 2009;Myhren et al, 2010aMyhren et al, , 2010bPeris et al, 2011;Garrouste-Orgeas et al, 2012;Wade et al, 2012;Rosendahl et al, 2013), whereas in others fewer symptoms were found, although still more than seen in the general population (Schelling et al, 1998;Cuthbertson et al, 2004;Nickel et al, 2004;Girard et al, 2007;Samuelson et al, 2007;Davydow et al, 2013;Svenningsen, 2013). In some studies, prior psychiatric disease was correlated with PTSD after ICU discharge (Nickel et al, 2004;Davydow et al, 2013), but not in all (Svenningsen, 2013), and anxiety and depression are sometimes described in combination with PTSD (Jones et al, 2004;Myhren et al, 2009;Myhren et al, 2010aMyhren et al, , 2010bGarrouste-Orgeas et al, 2012;Herbst and Drenth, 2012;Davydow et al, 2013;Rosendahl et al, 2013). In one qualitative study, patients suffering from PTSD described a need to make sense of their traumatic memories, and the transformation of one's self (Corrigan et al, 2007).…”
Section: Mental Conditionmentioning
confidence: 99%
“…Seeing the room and talking about hallucinations and dreams help patients to understand their unreal experiences (Corrigan et al, 2007;Engstrom et al, 2008;Storli et al, 2008). Narrating one's experiences in an ICU has the potential to minimize the risk of developing PTSD (Herbst and Drenth, 2012). The return visit appeared to be significant in the quest for meaning, and 'feeling' the room and the experiences of the ICU stay again could be integrated into life in a true way (Storli and Lind, 2009).…”
Section: Aftercarementioning
confidence: 99%
See 1 more Smart Citation
“…They recommend that staff explain medical procedures to the patient, talking continuously in a comforting and reassuring way; and that they be sensitive to the possibility that the patients can hear all conversations in the room 34. Confirming a similar approach, Samuelson argues that providing information, facilitating communication and arranging for the presence of family at the time of weaning may be helpful in reducing endotracheal tube related distress 17…”
Section: Introductionmentioning
confidence: 99%
“…In reference to Herbst and Drenth (2012 ), Rachatapantanakorn, Tongkumchum, and McNeil (2009 ), a report from the World Health Organization shows that more than 9 million neonatal deaths occur worldwide each year in the early weeks of life most of which are occuring in developing countries. So it is important to keep the infants as a vulenerable group in developing countries healthy by presenting better ways of taking care of them ( Amani, Barak, Amini, & Dehghan Mohammad, 2006 ).…”
Section: Introductionmentioning
confidence: 99%